The low self-efficacy trap: why people with vulnerabilities experience prolonged periods with payment problems - Kempson, Elaine; Poppe, Christian (Frontiers in Behavioral Economics, 2024)
Introduction Societies place a responsibility on individuals to pay what they owe on time, establishing a coercive apparatus for debt collection and enforcement when they do not, coupled with consumer protection and debt resolution measures to protect the vulnerable. Methods An analysis of in-depth interviews with 28 people with both payment difficulties and vulnerabilities from ill-health, using Bandura's Social Cognitive Theory to explore the experiences of vulnerable defaulters as they try to exercise the personal responsibility placed on them by society. Results It finds that they encounter barriers in exercising the personal responsibility which primarily arise in encounters with inflexible and bureaucratic routines – of creditors, debt enforcement agents and even money advisers whose role is to help vulnerable people. These systematically undermine defaulters' self-efficacy, and leaving them facing prolonged periods of payment difficulties. Discussion The findings are discussed in the light of Bandura's Theory and lessons drawn for the policies and practices of creditors, debt enforcement bodies, and money advisers.